Hidrotalcitas: síntese, caracterização e remoção de petróleo em efluentes aquosos - ALBUQUERQUE, Carla Cristina Vidal (2017)
Hydrotalcites were synthesized in the absence and presence of sucrose, and at temperatures of 28 oC (HDL and HDL / S) and 65 oC (HDL / S-65), by the coprecipitation method. All materials were characterized by ICPE, DRX, FTIR, MEV and BET. The general formulation obtained was: [Mg5.4Al2 (OH) 14.8] CO3.nH2O for all samples, confirming the success of the syntheses. The materials were used as adsorbents by two methods (Gravimetry and Turbidimetry), for the removal of petroleum from an emulsion in hydroalcoholic medium. The order of efficiency observed for a mass of 0.03 g of the adsorbents for the gravimetric method was: HDL/S-65 (92%) > HDL/S-28 (85%) > HDL (59%), indicating the positive effect of sucrose on the synthesis of the material. All the adsorptions followed a pseudo-second order kinetics, with an equilibrium time of approximately 50 min. Based on the results obtained by gravimetry it was understood that another method would be necessary, to better understand the behavior of the materials applied. The turbidimetry method showed favorable adsorption kinetics for the concentration used, showing that the process apparently occurred in multilayer, however complex. The models of Pseudofirst order, Pseudo-second order and intraparticle applied has favorable contributions to the understanding of these processes taking into account the several factors that influence the adsorption. The system also shows that HDL / S-28 has a higher removal capacity than HDL and HDL / S-65 respectively at 8h and 24h: HDL (8h) = 3538, HDL / S-28 (8h) = 3907; HDL / S-65 (8h) = 2127; HDL (24h) = 3252, HDL / S-28 (24h) = 5122; HDL / S-65 (24h) = 4201.